Kara ograniczenia wolności w świetle zmian po uchwaleniu ustawy z dnia 20 lutego 2015 roku o zmianie ustawy — Kodeks karny oraz niektórych innych ustaw, a także ustawy z dnia 11 marca 2016 roku o zmianie ustawy — Kodeks postępowania karnego oraz niektórych innych ustaw - Cendrowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The publication is devoted to the changes that the penalty of restriction of liberty underwent at the turn of 2015/2016. During that period, two acts were adopted: the Act of February 20, 2015 on the amendment to the Penal Code Act and certain other acts, then the Act of March 11, 2016 on the amendment to the Code of Criminal Procedure Act and certain other acts. The study presents the direction of changes which gives the penalty of restriction of liberty a greater prominence in terms of accomplishing the tasks of the criminal policy. The new formula the penalty of restriction of liberty took pursuesthe most essential goals of punishment, i.e. retributive and preventive, and at the same time does not burden the state with the costs associated with penitentiary isolation. The penalty of restriction of liberty, being one of the basic measures, is an effective tool inthe new regulation to fight petty and medium crime.
Keywords: penalty of restriction of liberty; probation officer; imprisonment; fine